Educational Supervision: Analysis of Learning the Qur'an Tilawati Method at User Institutions in Surabaya - Rt Bai Rohimah; Sholeh Hidayat; Suherman Suherman (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2024)
The Al-Qur'an tilawati learning method was developed to facilitate the study of the Al-Qur'an for Muslims. This research intends to examine the implementation of the tilawati technique in 5 Al-Quran learning institutions in Surabaya. This qualitative study employs descriptive approaches to elucidate and characterise supervision practices at five formal educational institutions in Surabaya that utilise the tilawati method. This study employed three data gathering methods: observation, interviews, and field documentation. This research includes data reduction, data display, and verification as part of the data analysis process. The research findings indicated that the Key Performance Area (KPA) was functioning efficiently in SD Khadijah 2 Surabaya, but was not meeting its intended purpose in the other four schools. The learning process does not correspond with the tilawati method. Teachers are inadequately trained to utilise this method. Attendance records, schedules, and achievements are not consistently shared with all teachers. Most classrooms have a layout of benches and tables with parallel shapes. The learning facilities are not fully developed in all elementary schools involved in the study. The tilawati method of learning has been implemented in 5 schools in Surabaya. The impact of implementing the tilawati method in schools is that students are more able to read the Al-Quran well and easily.